জহির রায়হান : অনুসন্ধান ও ভালোবাসা - রহমান, মতিউর (ঢাকা : প্রথমা প্রকাশন, 2021)
Articles on Jahira Rāẏahāna, 1934-1972, Bengali author and film maker from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Raihan, Zahir, -- 1935-1972.; Authors, Bengali -- 19th century -- Biography